Aleurocybotus mojavensis (Hemiptera: Sternorrhyncha: Aleyrodidae), a new whitefly species from California - Von Ellenrieder, Natalia; Bailey, James (Zootaxa, 2022)
A new species of Aleurocybotus Quaintance & Baker, 1914 found on grasses in the Mojave Desert in California, U.S.A., is described, figured, and diagnosed from its congeners. It can be easily recognized from A. occiduus Russell, 1964, the only other species of this genus present in California, by the copious white woolly wax secretions of its puparia and corresponding dorsal submarginal glandular band, and from A. cereus Martin, 2005, the only other Aleurocybotus species that produces large amounts of white wax, by its narrower glandular band, shape of vasiform orifice and operculum, and several other cuticular characters. A key to identify puparia of all described species of Aleurocybotus is provided.